2013
DOI: 10.1037/a0026293
|View full text |Cite
|
Sign up to set email alerts
|

Reducing courts' failure-to-appear rate by written reminders.

Abstract: This article examines the effectiveness of using different kinds of written reminders to reduce misdemeanor defendants' failure-to-appear (FTA) rates. A subset of defendants was surveyed after their scheduled court date to assess their perceptions of procedural justice and trust and confidence in the courts. Reminders reduced FTA overall, and more substantive reminders (e.g., with information on the negative consequences of FTA) were more effective than a simple reminder. FTA varied depending on several offens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…There is a growing literature on ways to improve the processes and outcomes associated with arraignments (e.g., Bock & Frazier ; Frazier et al ; Goldkamp & Gottfredson ; Bridges et al ; Demuth ; Devers ), even some studies based on randomized experiments (Goldkamp & White ; McElroy ; Bornstein et al ). Risk assessments have of late figured very significantly in these studies (VanNostrand & Keebler ; Arnold Foundation ), but the risks being forecasted are typically defined as an arrest for any crime.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing literature on ways to improve the processes and outcomes associated with arraignments (e.g., Bock & Frazier ; Frazier et al ; Goldkamp & Gottfredson ; Bridges et al ; Demuth ; Devers ), even some studies based on randomized experiments (Goldkamp & White ; McElroy ; Bornstein et al ). Risk assessments have of late figured very significantly in these studies (VanNostrand & Keebler ; Arnold Foundation ), but the risks being forecasted are typically defined as an arrest for any crime.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that simple reminders can improve FTA rates. One recent study that collected data from 14 counties in Nebraska found that defendants who were randomly selected to receive varying forms of a mailed reminder about appearance were more likely to appear than those who did not [ 19 ]. Additionally, reminders that included details about the potential penalties resulting from FTA (rather than the appearance alone) were found to enhance appearance rates even more.…”
Section: Introductionmentioning
confidence: 99%
“…Our study relates to an existing literature on low cost interventions to increase court case compliance, as well as a broader literature applying RCTs to legal issues (Greiner and Matthews, 2016). Previous RCTs have shown that reminders reduced FTA by 23 to 26 percent (Bornstein et al, 2013;Lowenkamp et al, 2018;Fishbane et al, 2019). These studies also find that emphasizing the consequences of FTA may be particularly effective, as defendants may be unaware or misinformed.…”
mentioning
confidence: 87%
“…A defendant who FTAs can face additional fines and fees, a driver's license suspension, and a warrant. FTAs also increase operational costs for the government (Bornstein et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation